1993
DOI: 10.1086/289749
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of Time-Symmetrized Quantum Mechanics

Abstract: In the context of a discussion of time symmetry in the quantum mechanical measurement process, Aharonov et al. (1964) derived an expression concerning probabilities for the outcomes of measurements conducted on systems which have been pre- and postselected on the basis of both preceding and succeeding measurements. Recent literature has claimed that a resulting “time-symmetrized” interpretation of quantum mechanics has significant implications for some basic issues, such as contextuality and determinateness, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…Perhaps more importantly, Sharp and Shanks [SS93], and Cohen [Coh95] demonstrated that attempting to combine post-selective inferences when Bob's measurements disturb Alice's measurement results, will in general lead to inconsistent probabilistic predictions.…”
Section: Non-detectable Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps more importantly, Sharp and Shanks [SS93], and Cohen [Coh95] demonstrated that attempting to combine post-selective inferences when Bob's measurements disturb Alice's measurement results, will in general lead to inconsistent probabilistic predictions.…”
Section: Non-detectable Measurementsmentioning
confidence: 99%
“…As the paradigm example of a quantum pre-and post-selection (PPS) paradox there has been much discussion of its meaning. Questions raised include the validity of the counterfactual use of the ABL rule [SS93,Coh95,Kas03], connections to quantum contextuality proofs and measurement disturbance [LS05b,LS05a] and whether classical systems can simulate the essential properties of a PPS paradox [Kir03,LS05a].…”
Section: Introductionmentioning
confidence: 99%
“…Ruth Kastner [4,5,6] and others [7,8,9] have raised objections concerning the appropriateness of probability assignments to counterfactuals based on the ABL rule. The first objection I will address is this [6]: Since the Q measurement is not actually made, the following rule should be used instead of the ABL rule (6):…”
Section: Reply To Kastnermentioning
confidence: 99%
“…That she thinks differently about the background conditions is obvious from her discussion [5] of the experiment considered by Sharp and Shanks [7]. In this experiment spin- 1 2 particles are prepared at time t 1 with probability measure |a + and subjected at time t 2 to a measurement of their spin component along the b axis.…”
Section: Reply To Kastnermentioning
confidence: 99%
See 1 more Smart Citation